Optimisation and application of a method designed to assess host DNA in pig and poultry faeces as a potential marker of gut cell loss - Slinger, Kimberley R. (2020)
Maintaining and replenishing the intestinal barrier is an energy demanding process. In farmed species the excessive energy utilised by this process could be better utilised in the production of proteins for lean muscle deposition, milk synthesis or egg production. Altering the diets of farmed animals can improve how efficiently feed energy is converted into useful product. Therefore, it would be useful to examine how any nutritional changes impact upon gut function, particularly gut cell turnover which utilises such a significant proportion of dietary energy. Currently all methods to assess gut turnover in farmed species are invasive to some extent and typically very expensive, therefore, there is scope to develop a novel non-invasive method that could potentially be used routinely in a farm setting. Sloughed epithelial cells are broken down in the lumen of the intestine by endonucleases, presumably leading to fragmented host DNA being present in the faeces. This thesis developed methodologies for analysing faecal host DNA from pig and chicken faeces and the developed protocols were then applied to feeding studies where differences in gut cell sloughing were expected.